Kapasitas Badan Penanggulangan Bencana Daerah Karo Dalam Penanganan Rumah Relokasi Siosar Tahap I - Impala Octaviani Br Surbakti; Rudi Kristian P Manurung (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This study aims to determine and describe how the Karo Regional Disaster Management Agency's Capacity in Handling Siosar Relocation Houses Phase I, with a descriptive method with a qualitative approach that explains the phenomenon in depth through data collection such as interviews, observations, documentation, and literature studies. In this study, we used Horton's theory with indicators of organizational capacity assessment, including human resources, infrastructure, technology and financial resources, strategic leadership, programs and management, network cooperation and relationships with other parties. Through this study, researchers found that the capacity of the Karo Regional Disaster Management Agency in handling Siosar Phase I Relocation Houses was not maximized, judging from the indicators of human resources that were not maximized, where the educational background of employees was not in accordance with position placement, related to infrastructure, technology, and resources. related to the chief executive's strategic leadership not interacting with employees; related to programs and management where lack of knowledge causes errors in writing sub-districts in house certificates in stage I; and related to relationships with other parties that are not good due to a lack of communication and coordination, resulting in a lack of communication.